Entrepreneurship Spirit and Entrepreneurship Value Enhancing Entrepreneurial Independence Through Entrepreneurial Behavior - Arviana Wulandari; Suroyo Suroyo (International Journal of Education, Information Technology, and Others, 2020)
The difficulties of small enterprise need to be anticipated by conducting empirical testing through a study of the spirit of entrepreneurship, entrepreneurship values, and studies of entrepreneurial behavior that can affect the process of achieving entrepreneurial independence. This study aims to analyze the influence of entrepreneurship spirit and entrepreneurship values ​​on entrepreneurial behavior to create entrepreneurial independence. The method used in analyzing data was Path Analysis. The sample in this study was 125 small entreprises consisted of 45 small enterprises of Batik Pekalongan, 42 small enterprises of traditional foods Batu Malang and 38 small enterprises of Ceramic Kasongan Bantul Yogyakarta. The data analyzed using Structural Equation Modeling (SEM). The test results showed that the spirit of entrepreneurship had a direct influence on entrepreneurial behavior and an indirect effect on entrepreneurial independence. Entrepreneurship value had a direct influence on entrepreneurial behavior and also indirectly affects entrepreneurial independence. While entrepreneurial behavior had a positive effect on business independence.